Ethnoscience of Salt Production: Relevance of Local Knowledge to Scientific Principles - Nurul Hidayah; Lalu Muhammad Rispan Sugi Saputra; Agil Al Idrus; Agus Abhi Purwoko (Indonesian Publication Center, 2025)
This study aims to identify the relevance of the traditional knowledge of Pijot Village, East Lombok, with scientific concepts in the salt-making process and explore how this practice can be integrated into science education through an ethnoscience approach. The research employed a qualitative method using observation and interviews to gather in-depth data on the stages and local knowledge applied in salt production. The findings reveal that the salt-making process, including evaporation and crystallization, aligns with scientific concepts of phase changes. The use of solar energy in evaporation also reflects renewable energy concepts taught in science education. Integrating ethnoscience into science lessons helps students understand scientific concepts contextually and meaningfully, enhancing both science literacy and creative thinking skills. However, the implementation of ethnoscience faces challenges, such as limited learning media and teachers' understanding of the approach. Therefore, teacher training and the development of ethnoscience-based student worksheets (LKPD) are essential to facilitate learning. The study’s findings are expected to promote curriculum development that links scientific concepts with local culture, enabling students to better apply their knowledge in real-life contexts.